2019
DOI: 10.1093/hmg/ddz090
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific sex differences in human gene expression

Abstract: Despite extensive sex differences in human complex traits and disease, the male and female genomes differ only in the sex chromosomes. This implies that most sex-differentiated traits are the result of differences in the expression of genes that are common to both sexes. While sex differences in gene expression have been observed in a range of different tissues, the biological mechanisms for tissue-specific sex differences (TSSDs) in gene expression are not well understood. A total of 30 640 autosomal and 1021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 56 publications
2
52
0
Order By: Relevance
“…Two studies on sex differences in the liver transcriptome reported 844 and 1,249 sex-biased genes, respectively 22,23 . These numbers are in the same order of magnitude as what we report here for endothelial cells, highlighting that sex influences the transcriptome over variety of tissues, as underlined by work in the Genotype-Tissue Expression project 6,7 . Furthermore, sex differences in expression might also underlie differences between the sexes in response to stimuli or disease.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Two studies on sex differences in the liver transcriptome reported 844 and 1,249 sex-biased genes, respectively 22,23 . These numbers are in the same order of magnitude as what we report here for endothelial cells, highlighting that sex influences the transcriptome over variety of tissues, as underlined by work in the Genotype-Tissue Expression project 6,7 . Furthermore, sex differences in expression might also underlie differences between the sexes in response to stimuli or disease.…”
Section: Discussionsupporting
confidence: 80%
“…Transcriptomic studies of female and male (endothelial) cells shed light on differentially expressed genes (DEGs) between the sexes and their regulators, but few have been performed thus far on ECs 4 . Tissue-specific comparisons have been made using publicly available data from the Genotype-Tissue Expression project 6 , 7 , showing the importance of looking at sex differences in transcriptomics, but it may be difficult to extrapolate this to individual cell-types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, Huggett and Stallings have identified a SNP associated with cocaine dependence and detected three genes (two loci) underlying this predisposition that displayed robust enrichment in numerous brain regions, including the hippocampus . Gene expression genetic analyses in the GTEx project show sex differences in genetic regulation of gene expression in both reproductive and nonreproductive tissues, providing an important means of evaluating the mechanisms through which sex‐specific genetic loci might act. This approach was recently used to interpret the male‐specific effects of an opioid dependence‐associated variant …”
Section: Sex Differences In Human Genomic Studies Of Addictionmentioning
confidence: 99%
“…group 3, see above) and inactive in the tissues where they are not. For example, genes could be activated in ovary, but inactivated by regulatory mechanisms other than DNA methylation in RBCs (Campbell & Langlois 2018;Kassam et al 2019;Miragaia et al 2019).…”
Section: Discussionmentioning
confidence: 99%